PAI Learning Strategy for Graduate Students at Extraordinary Junior High Schools in Tangerang - Sukanti, Lina; Kumar, Saurav (The International Journal of Education Management and Sociology, 2023)
This research aims to find strategies, methods, evaluations, media, and obstacles to implementing PAI for mentally retarded students at SMPLB Negeri. The research method uses qualitative analysis. Data sources are PAI teachers, administrative staff, and students' parents. Data collection techniques were carried out through observation, interviews, and document review. Data analysis was carried out by reducing data, presenting data, and drawing conclusions. The findings in this research are (1) PAI learning strategies with expository and contextual strategies on the cognitive aspect, value clarification technique strategies on the affective aspect, and direct learning strategies on the psychomotor aspect. (2) PAI learning methods are the lecture model, question and answer model, demonstration model, and exemplary model. (3) PAI learning media is prayer equipment, namely sarongs, mukenas, prayer mats, and prayer rooms. (5) Evaluation of PAI learning using the question-and-answer model and memorization tests. Written test and oral test models. Meanwhile, the non-test technique is observation. (6) Obstacles to PAI learning are students' limitations in remembering lessons, students' limited language skills, students' lack of discipline during school hours, and the absence of accompanying teachers.